Exploring the Ruddlesden–Popper layered organic–inorganic hybrid semiconducting perovskite for visible-blind ultraviolet photodetection. Issue 12 (25th February 2022) - Wang, Yuyin; Su, Bin; Lin, Guoming; Lou, Huiru; Wang, Shouxin; Yue, Cheng-Yang; Lei, Xiaowu
Abstract : An R–P type two-dimensional hybrid perovskite (C8 H11 FN)2 PbBr4, which exhibits spectral selective photoresponse for UV light. Abstract : Compared to the three-dimensional (3D) perovskite materials, the Ruddlesden–Popper (R–P) type two-dimensional (2D) organic–inorganic metal halide perovskites have indicated specific unique physical properties that include moisture-stable behaviours, exciton effects, and quantum confinements, making it a solid and potential candidate for optoelectronic applications. Nonetheless, while specific candidates have exhibited visible-blind ultraviolet (UV) photoelectric response, most R–P type 2D materials have been known to be photosensitive to visible light. In this study, an R–P type 2D lead bromide hybrid perovskite (C8 H11 FN)2 PbBr4, (1, where C8 H10 FN is 4-fluorophenethylamine) has been analyzed, which contained both inorganic frameworks and organic cations. Moreover, 1 exhibits a relatively wide optical bandgap of 3.30 eV, corresponding to that of the Br-based 2D R–P perovskites expected to exhibit selective photoresponse for the UV light. It is pertinent to note that the photodetectors based on the crystal of 1 exhibit spectral selective photoresponse for UV light with high detectivity up to ∼1.6 × 10 11 Jones. Moreover, the trap density of 1 is estimated to be 1.34 × 10 11 cm −3 ; the trap density of 1 was almost equal to that obtained in the high-quality 3D CH3 NH3 PbBr3 single crystals. Besides, under external environment, 1 illustrated excellent stability. The figures of merit for its photoconductivity make 1 a potential candidate for the visible-blind UV photodetection. This discovery opens up new vistas for the further development of optoelectronic devices based on 2D R–P organic–inorganic hybrid perovskites.